The Approaches teachers employ in addressing the common grammatical errors of two sixth grade sections in the University of the Philippines Integrated School - Gammad, Joan Mary Hyacinth I.; Guaring, Arvie Jean B. (College of Arts and Letters, University of the Philippines Diliman, 2004)
This theses focuses on how teachers address grammatical errors as they are armed with their knowledge of the different approaches in language teaching. Several issues are raised in this research. First in line is the question of which approach is more effective in addressing grammatical errors. However, the Communicative Approach and the traditional approaches are the only approaches presented, with emphasis on each approach's regard for errors. Secondly, this thesis takes into consideration that a teacher's personality and beliefs in language teaching also affect her methods and techniques in error correction, not only the approach she subscribes to. Thirdly, the pupils' responses to their teacher's choice of approach are also considered in this thesis. Indeed, through experience and solid eclectic theoretical foundations, a teacher will be able to discern which approach is appropriate at given moments.